CHARACTERISTICS AND OUTCOMES OF CONTINUOUS RENAL REPLACEMENT THERAPY IN CHILDREN AT THE NATIONAL CHILDREN’S HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe characteristics, techniques, clinical conditions, and the outcomes of patients treated by continuous renal replacement therapy.Subjects and methods: A cross-sectional descriptive study was conducted on 340 pediatric patients who underwent continuous renal replacement therapy (CRRT) at the Pediatric Intensive Care Unit, Vietnam National Children’s Hospital from January 2018 to June 2021.Results: Sepsis was the most common conditions requrired CRRT (56.76%), followed by metabolic disorders (13.53%) and cardiogenic shock (8.24%). Continuous venovenous hemofiltration (CVVH) was the predominant modality (90.29%). The most common complications were hypokalemia (68.82%), filter clotting (52.06%), and hypotension (47.65%). The survival rate was 56.18%. Multivariable analysis showed that PELOD-2 score and the time from Intensive Care Unit admission to CRRT initiation were independently associated with mortality (p < 0.05).Conclusions: CRRT is mainly used in pediatric patients for  sepsis and multiple organ dysfunction. Although complications are common, they are generally manageable. Disease severity and timing of CRRT initiation are important factors influencing treatment outcomes.
Keywords: Continuous renal replacement therapy, CRRT, pediatrics, complications, outcomes.